Prevalence and zoonotic risk factors of Mycobacterium bovis tuberculosis in cattle at the cattle-wildlife-human interface in South and East Cameroon - Kouengoua Kouengoua, Armelle Prudence; Tsissa, Yves Ledoux; NOUDEKE, NESTOR; Chimi, Roland Nankam; Njayou, Arouna; Abdou Karim Youssao, Issaka; Mahamadou Dahouda, Mahamadou Dahouda; BOKO, KADOÉITO CYRILLE; Dougnon, Tamègnon Victorien; Awah-Ndukum, Julius; Farougou, Souaibou (My University, 2024)
Background and Aim: Bovine tuberculosis (bTB) is a contagious and notifiable disease, which is prevalent in cattle populations of many countries and in several wildlife species worldwide. However, the role of wildlife in the transmission and/or maintenance of bTB at the human-wild animal-animal interface and the epidemiology of zoonotic disease are poorly understood in Cameroon, where many wildlife species exist. This study aimed to estimate the prevalence and zoonotic risk factors of bTB at the cattle-wildlife-human interface in the South and East regions of Cameroon. Materials and Methods: We conducted a descriptive cross-sectional study from May to October 2022 in the southern region (Vallée du Ntem and Dja et Lobo) and eastern region (Haut Nyong and Lom et Djérem) of Cameroon to determine risk factors for bTB in Zebu Bororo, Goudali, Ndama, and Simmental cattle breeds. A comparative intradermal tuberculin testing (CIDT) was performed on 160 cattle randomly selected from herds using the threshold recommended by the World Organization for Animal Health. An interviewee-administered questionnaire was used to gather epidemiological data on sociodemographics, interaction between cattle and wildlife, and awareness of zoonotic tuberculosis (TB) from 90 cattle professionals. The prevalence of bTB at the herd level and associated risk factors were estimated using multiple logistic regression models. Results: Based on the comparative intradermal tuberculin test (CIDT), the estimated prevalence of bTB in 160 cattle (Zebu Bororo, Goudali, Ndama, and Simmental) in South and East Cameroon was 6.8% (4.35%–9.41%) and 1.8% (0%–3.6%) for threshold values 3 mm and 4 mm, respectively. The prevalence obtained by simple intradermal tuberculin test (IDT) was 0.6% (0%–1.2%) for a threshold value 4 mm. Univariate analysis revealed three risk factors associated with bTB with significant odds ratios (OR; p = 0.05): herd size (OR = 4.88; 95% confidence interval [CI]: 1.24–32.56); cattle aged>10 years (OR = 0.17; 95% CI: 0.05–0.53); and victims of bTB organ seizure (OR = 0.015; 95% CI: 0.002–0.067). Multivariate analysis showed that being a cattle herder and contact between wildlife and livestock due to forage was significantly associated with bTB exposure (adjusted OR = 0.02; p = 0.001). Conclusion: Bovine TB is prevalent in cattle of the South and East Cameroon. Comparative IDT of cattle reared in the epidemiological and environmental context of the study areas yielded better results at a threshold of 3 mm than at a threshold of 4 mm recommended by the World Health Organization. Factors associated with exposure to/appearance of bTB were high herd size, cattle aged >10 years old, seizures of tuberculous organs, shepherding as a profession, and contact between cattle and wildlife can be due to lack of forage.
Keywords: bovine tuberculosis prevalence; East and South Cameroon; livestock-wildlife-human interface; zoonotic risk; factors